1998
DOI: 10.1103/physrevd.58.114508
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical approximation for non-Abelian field strength correlators in the instanton dilute gas model

Abstract: Field strength correlators are semi-classically evaluated in the dilute gas model of non-Abelian sources (instantons) and compared with lattice data for QCD at zero temperature. We show that one of the Euclidean invariant, tensorial structures vanishes for configurations being purely selfdual or antiselfdual. We compute the invariant functions contributing to the correlators within the two lowest orders in an instanton density expansion. Fitting instanton size and density for quenched and full QCD, we obtain a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
1
2

Year Published

1998
1998
2002
2002

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 33 publications
0
26
1
2
Order By: Relevance
“…RG-smoothing by our method does not lead to classical configurations. Clustering of topological charge and action in dominantly (anti)selfdual clusters [3] is a property of SM lattice fields inherited from the MC vacuum. Smoothed fields preserve the string tension, its Abelian dominance and contain a topological susceptibility of the right magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…RG-smoothing by our method does not lead to classical configurations. Clustering of topological charge and action in dominantly (anti)selfdual clusters [3] is a property of SM lattice fields inherited from the MC vacuum. Smoothed fields preserve the string tension, its Abelian dominance and contain a topological susceptibility of the right magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, we shall elaborate out one of such possibilities. To this end, we shall make use of recent results concerning the calculation of the field strength correlators in the dilute instanton gas model [9]. There it has been demonstrated that for the case of an instanton gas with broken CP invariance, the bilocal field strength correlator contains a term proportional to the tensor ε µνλσ .…”
mentioning
confidence: 99%
“…They are the basic quantities in models of stochastic confinement of color [4,5,6] and in the description of high-energy hadron scattering [7,8,9,10,11,12,13]. In some recent works [14,15], these correlators have been semi-classically evaluated in the single-instanton approximation and in the instanton dilute-gas model, so providing useful information about the role of the semiclassical modes in the QCD vacuum.…”
Section: Introductionmentioning
confidence: 99%